PARP-1 deregulation in multiple sclerosis. Issue 4 (December 2019) - Meira, Maria; Sievers, Claudia; Hoffmann, Francine; Bodmer, Heidi; Derfuss, Tobias; Kuhle, Jens; Haghikia, Aiden; Kappos, Ludwig; Lindberg, Raija LP
Background: Poly (ADP-ribose) polymerase 1 (PARP-1) plays pivotal roles in immune and inflammatory responses. Accumulating evidence suggests PARP-1 as a promising target for immunomodulation in multiple sclerosis and natalizumab-associated progressive multifocal leukoencephalopathy. Objective: This study explores expression of PARP-1 and downstream effectors in multiple sclerosis and during natalizumab treatment. Methods: Transcriptional expressions were studied by real-time reverse transcriptase polymerase chain reaction on CD4 + T/CD8 + T/CD14 + /B cells and peripheral blood mononuclear cells from healthy volunteers, untreated and natalizumab-treated non-progressive multifocal leukoencephalopathy and progressive multifocal leukoencephalopathy multiple sclerosis patients. Results: PARP-1 expression was higher in CD4 + T, CD8 + T and B cells from untreated patients compared to healthy volunteers. Natalizumab treatment restored deregulated PARP-1 expression in T cells but not in B cells. Sustained upregulation of PARP-1 was associated with decreased expression of downstream PARP-1 factors such as TGFBR1/TGFBR2/BCL6 in B cells. Notably, a higher expression of PARP-1 was detected in progressive multifocal leukoencephalopathy patients. Conclusions: Given the importance of PARP-1 in inflammatory processes, its upregulation in multiple sclerosis lymphocyte populations suggests a potential role in the immune pathogenesis of multiple sclerosis. Strikingly higher PARP-1 expression in progressive multifocal leukoencephalopathy cases suggests its involvement in progressive multifocal leukoencephalopathy disease pathomechanisms. These results further support the value of PARP-1 inhibitors as a potential novel therapeutic strategy for multiple sclerosis and natalizumab-associated progressive multifocal leukoencephalopathy.